SHARING LITERASI KEWIRAUSAHAAN: PROGRAM PEMBUATAN SABLON DI DINAMIKA KONVEKSI PONOROGO - Titis Purwaningrum; Alip Sugianto; Riyantika D (Jurnal Utilitas, 2022)
Ponorogo is a cultural city that is famous for its reyog art. This art has been worldwide in various countries. To support Ponorogo as a cultural city that has tourism value, it needs to be supported by souvenirs as part of souvenirs, but not many souvenirs have been produced from Ponorogo SMEs so that they are not maximized. Therefore, this great opportunity needs to be captured by local entrepreneurs, one of the souvenirs that have the opportunity is ethnic screen printing shirts with rigged patterns and so on. This requires synergies and sharing of screen printing programs with several stages, so that it is hoped that it will result in strengthening entrepreneurship and making MSMEs stronger and more competitive.